Analysis Analisis Tingkat Kebahagiaan Perawat Menggunakan Metode Oxford Happiness Questionnaire di Puskesmas Kabupaten Gowa - Risnawati; Hasanuddin, Rahma (PT.Mantaya Idea Batara, 2025)
As part of professional healthcare workers, nurses play an essential role as caregivers, educators, client advocates, counselors, agents of change, leaders, managers, case managers, researchers, and developers of nursing practices. However, the number of nursing staff still needs to meet national targets, resulting in suboptimal nurse performance and increased workloads. The rising workload for nurses can cause work fatigue, which can affect the nurse's happiness. Unhappy nurses will affect their productivity at work, especially in providing quality care and services. to determine the level of joy among nurses at the Gowa District Health Center. The research design is descriptive, quantitative, and categorical. The sampling technique used is total sampling. This research was conducted from February to April 2024 in the Public Health Center in Gowa Regency, consisting of 71 respondents. The data collection method used was The Oxford Happiness Questionnaire (OHQ). The research findings indicate that all 71 respondents (100%) have a very high level of happiness.Based on the research results, it is known that the happiness level of nurses in the Public Health Center in Gowa Regency is in the very high category